Integration of Emission-wavelength-controlled InAs Quantum Dots for Ultrabroadband Near-infrared Light Source - Nobuhiko Ozaki; Koichi Takeuchi; Yuji Hino; Yohei Nakatani; Takuma Yasuda; Shunsuke Ohkouchi; Eiichiro Watanabe; Hirotaka Ohsato; Naoki Ikeda; Yoshimasa Sugimoto; Edmund Clarke; Richard A. Hogg (Nanomaterials and Nanotechnology)
Near-infrared (NIR) light sources are widely utilized in biological and medical imaging systems owing to their long penetration depth in living tissues. In a recently developed biomedical non-invasive cross-sectional imaging system, called optical coherence tomography (OCT), a broadband spectrum is also required, because OCT is based on low coherence interferometry. To meet these operational requirements, we have developed a NIR broadband light source by integrating self-assembled InAs quantum dots (QDs) grown on a GaAs substrate (InAs/GaAs QDs) with different emission wavelengths. In this review, we introduce the developed light sources and QD growth techniques that are used to control the emission wavelength for broadband emission spectra with center wavelengths of 1.05 and 1.3 μm. Although the strain-induced Stranski-Krastanov (S-K) mode-grown InAs/GaAs QDs normally emit light at a wavelength of around 1.2 μm, the central emission wavelength can be controlled to be between 0.9–1.4 μm by the use of an In-flush technique, the insertion of a strainreducing layer (SRL) and bi-layer QD growth techniques. These techniques are useful for applying InAs/GaAs QDs as NIR broadband light sources and are especially suitable for our proposed spectral-shape-controllable broadband NIR light source. The potential of this light source for improving the performance of OCT systems is discussed.